Strength of high-strength wall under lateral loading - Mohammad Redha Mohd Said. (2012)
Recently, high strength concrete (HSC) had seen increasing number of applications in the construction industry. High strength reinforced concrete (RC) shear walls had been used in the construction of core walls in tall buildings. Due to its relatively high resistance against in-plane lateral and vertical loading, shear walls had proven to be effective in improving the seismic performance of buildings. However, many provisions for wall in the current design codes are based on experiments using normal strength concrete (NSC). The confidence level on the applicability of the equations provided by the codes needs to be raised to same level for other structural members such as beam and column.